Visual cultures in science and technology a comparative history - Hentschel, Klaus (Oxford, United Kingdom Oxford University Press, 2018)
"This book aims to provide a synthesis of the history, generation, use, and transfer of images in scientific practice. It delves into the rich reservoir of case studies on visual representations in scientific and technological practice that have accumulated over the past couple of decades by historians, sociologists, and philosophers of science. The main aim is thus located on the meta-level. It adopts an integrative view of recurrently noted general features of visual cultures in science and technology, something hitherto unachieved and believed by many to be a mission impossible. By systematic comparison of numerous case studies, the purview broadens away from myopic microanalysis in search of overriding patterns. The many different disciplines and research areas involved encompass mathematics, technology, natural history, medicine, the geosciences, astronomy, chemistry, and physics. The chosen examples span the period from the Renaissance to the late 20th century. The broad range of visual representations in scientific practice is treated, as well as schooling in pattern recognition, design and implementation of visual devices, and a narrowing in on the special role of illustrators and image specialists."--
1:Introduction-- 2:Historiographic layers of visual science cultures-- 3:Formation of visual science cultures-- 4:Pioneers of visual science cultures-- 5:Transfer of visual techniques-- 6:Support by illustrators and image technicians-- 7:One image rarely comes alone-- 8:Practical training in visual skills-- 9:Mastery of pattern recognition-- 10:Visual thinking in scientic and technological practice-- 11:Recurrent color taxonomies-- 12:Aesthetic fascination as a visual culture's binding glue-- 13:Issues of visual perception-- 14:Visuality through and through--
Includes bibliographical references and index
Keywords: Scientific illustration; Visual communication in science